Editor's Comments - Kilduff, Martin (Academy of Management Review, 2007)
The article explains the review process used on papers submitted for publication in the “Academy of Management Review” (AMR). The author also praises the reviewers who conduct the challenging and time consuming assessments. In consideration of the outstanding efforts of the reviewers and their contribution to management theory development, the first AMR Best Reviewer Award was instituted for 2005–2006. The winners chosen included Roy Suddaby of the University of Alberta School of Business, Olav Sorenson of the London business School, Dovev Lavie of the University of Texas at Austin, and Richard Whittington of Oxford University.